Sudden cardiac death associated with premature atheroma in the young: an autopsy study emphasising single-vessel lesions. (21st July 2015) - Green, Anna C.; Sheppard, Mary N.
Abstract: Aims: This is the first autopsy study in the United Kingdom to analyse the demographic and pathological characteristics of atheroma associated with sudden cardiac death in young people. Methods: An observational retrospective study of referred cases of sudden cardiac death in the young (⩽35 years) associated with premature atheroma was carried out. Results: In total, 46 cases were referred, with a median age of 30 years (27, 32); 72% of the referred cases were male, with a mean body mass index of 30 kg/m 2 . Circumstances of death were as follows: at rest (n=21), exertion (n=7), in bed (n=7), related to drugs/alcohol (n=4), and unknown (n=7). A previous cardiac history was provided in 10 cases. A history of class A/B drug use was found in eight cases. There was macroscopic evidence of infarction in 10 cases (acute, n=3 and chronic, n=7). Microscopically, 10 cases demonstrated contraction band necrosis, 11 acute infarction, and 11 chronic infarction. Single-vessel disease predominated (n=28). The left anterior descending coronary artery was involved in 39/46 cases. Thrombosis was seen in 16 cases, mainly due to erosion; one case showed dual pathology with arrhythmogenic right ventricular cardiomyopathy and another showed left ventricular hypertrophy. Conclusions: This study highlights premature atheroma mainly in a single vessel in young people with or without evidence of ischaemic damage in the ventricle. Dual pathology may occur. The role of arrhythmias and channelopathies are important considerations. Premature atheroma should prompt investigation for dyslipidaemias in family members.